Expansive Design for Teachers : An activity theoretical approach to design-based research - Augustsson, Dennis (EDeR. Educational Design Research, 2021)
Innovative designs for learning have implications for the teaching practices and the system in which they are created, often with conflicting motives and tensions on systemic levels. Co-design processes with teachers and researchers require tools and concepts to grasp this complexity and to create durable changes. In the case studied in this article, activity theory and change laboratory methodologies were used in a participatory design process with a small group of teachers. Five key characteristics of the epistemological principles behind the change laboratory methodology were identified and analysed. The theoretical framework enabled tools for a collective analysis of the origin and development of systemic contradictions as well as a model to envision future practices and concrete learning designs. Findings suggest that the combination of participatory design and change laboratory methodologies can serve as a vehicle for expansive learning and new innovative learning designs in educational settings.